Pediatric Blood Cancer Survivors and Tobacco Use across Adolescence and Emerging Adulthood: A Narrative Review - Masiero, Marianna; Riva, Silvia; Fioretti, Chiara; Pravettoni, Gabriella (Frontiers in Psychology, 2016)
Scholars underline the pivotal role of tobacco cigarette smoking in carcinogenesis process for blood tumors. A controversial debate is represented by the diffusion of tobacco use in young cancer survivors that had a previous diagnosis of blood tumor during the childhood. Compared with their peers, scientific evidence highlights that pediatric survivors have more difficult to give-up cigarette smoking. Furthermore, tobacco-smoking is frequently linked with others risk behaviors as drinking or substance abuse. In reviewing the main knowledge on this topic, authors affirm the need for increasing research on blood cancer survivors in order to depict psychological characteristics of pediatric blood cancer survivors. Improving health decision-making skills in young survivors could reduce the risk to adopt un-healthy behaviors and increase psychological wellbeing. Furthermore, authors propose tailored antismoking interventions based on the knowledge of the psychological and cognitive factors that support smoking during the transition toward emerging-adulthood.